Comparison of Modified Ashworth Scale and Hoffmann Reflex in Study of Spasticity - Amir Hassan Kohan; Shahram Abootalebi; Alireza Khoshnevisan; Mehdi Rahgozar (Acta Medica Iranica, 2010)
"nSpasticity is one of the common complications in upper motor neuron lesions and without appropriate treatment it causes disturbances in movement pattern. Assessments of patients are effective in patient`s management. Modified Ashworth scale (MAS) is one of the criteria in qualitative assessment of spasticity, and there are lots of controversies about its validity. The purpose of this study is to compare MAS with electrophysiological indices of spasticity. The spasticity of upper limb muscles in patients with hemiplegic cerebral palsy are measured and recorded by MAS. Then electrophysiological indices of Hoffmann reflex (H reflex) and ratio of maximum range of action potential of combined movement of flexor carpi radialis (FCR) for upper limb and soleus for lower limb were estimated. Data of 11 patients with age range 4 to 6 were analyzed. There is no significant correlation between degree of spasticity and electrophysiological indices.